2019
DOI: 10.1021/acs.macromol.8b02641
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Controlled Voltage Responsive Micelles Assembled by Noncovalently Grafted Polymers for Controlled Drug Release

Abstract: Voltage responsive micelles prepared from noncovalently grafted amphiphilic polymers were reported. The noncovalent amphiphilic polymers were prepared through the host–guest interaction between β-cyclodextrin (β-CD) grafted dextran (Dex-CD) and ferrocene (Fc) terminated poly­(ε-caprolactone) (PCL-Fc). Because of the presence of Fc groups, the inclusion complex between Fc and β-CD can be reversibly controlled by an external stimulating voltage, leading to reversible formation and disassembly of the micelles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…DPA is a well‐known ligand for lanthanide ions, and the characteristic sharp‐lines of the Eu(III) emission at 615 nm after excitation of DPA at 280 nm (antenna effect) corroborate that βCD‐DPA coordinates to the metal ion (Figure S6). The host‐guest interaction between βCD and adamantane has been extensively demonstrated previously, so Ad‐SS‐Ad molecules were designed to link two coordination complexes, driving the formation of branched oligomeric structures. By adding a block copolymer (P2MVP 128 ‐b‐PEO 477 ) composed of a positively‐charged part and a neutral part to the negatively‐charged oligomeric units, Ad‐SS‐Ad‐based C4Ms were formed, (Figure S10).…”
Section: Resultsmentioning
confidence: 92%
“…DPA is a well‐known ligand for lanthanide ions, and the characteristic sharp‐lines of the Eu(III) emission at 615 nm after excitation of DPA at 280 nm (antenna effect) corroborate that βCD‐DPA coordinates to the metal ion (Figure S6). The host‐guest interaction between βCD and adamantane has been extensively demonstrated previously, so Ad‐SS‐Ad molecules were designed to link two coordination complexes, driving the formation of branched oligomeric structures. By adding a block copolymer (P2MVP 128 ‐b‐PEO 477 ) composed of a positively‐charged part and a neutral part to the negatively‐charged oligomeric units, Ad‐SS‐Ad‐based C4Ms were formed, (Figure S10).…”
Section: Resultsmentioning
confidence: 92%
“…The results suggested that the supramolecular ion assembly between β-CD and Fc would be beneficial to the mechanical properties of the hydrogels. The supramolecular ion assembly of a copolymer containing β-CD and Fc moieties has also been studied and the redox-switchable properties of the copolymer have been confirmed in the electrochemical response of the Fc moieties [41], conferring voltage-controllable assembly and disassembly features to the samples [42].…”
Section: Introductionmentioning
confidence: 98%
“…The unique electrochemical, physicochemical, magnetic, and optical properties of ferrocene (Fc)‐containing polymers have attracted widespread concerns in the fields of molecular battery, amperometric biosensors, sensors, nanopatterns, drug delivery, electrochromics, and catalysis . Particularly, Fc‐containing polymers could be used as reducing agents to prepare MNPs .…”
Section: Introductionmentioning
confidence: 99%